Penilaian Risiko Kebisingan di Area Kerja Industri Farmasi Pasuruan - Sari, Revita Dea; Martiana, Tri; Ardyanto, Denny (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Noise risks in the work area of the pharmaceutical industry in Pasuruan can have a negative impact on workers' health. The purpose of this study was to measure noise levels, evaluate health risks, and assess the effectiveness of noise control programs. The method used was descriptive analytic with a cross-sectional design, noise measurements were made using a sound level meter to obtain continuous sound pressure levels (Leq). Data were also analyzed using a risk matrix and field observations to identify noise sources. The results showed that the highest noise level in the work area reached 90 dBA, with the main sources coming from the generator and chiller engines, while most of the work area had a relatively low noise risk. Nevertheless, there are several points that exceed the established noise threshold. This study recommends the implementation of technical and administrative controls, including the use of personal protective equipment (PPE) and proper work scheduling, to reduce noise exposure. Periodic monitoring is also recommended to ensure the effectiveness of the applied controls, so as to create a safer working environment for workers.